2023
DOI: 10.1002/alr.23250
|View full text |Cite
|
Sign up to set email alerts
|

Does air pollutant exposure impact disease severity or outcomes in chronic rhinosinusitis?

Abstract: BackgroundPoor air quality increases the risk of developing chronic rhinosinusitis (CRS) and other airway diseases. However, there are limited data on air pollutants and CRS‐specific disease severity. We assessed the impact of air pollutants on sinonasal‐specific and general quality‐of‐life (QOL) measures in a multi‐institutional cohort of patients with CRS.MethodsParticipants with CRS were prospectively enrolled in a cross‐sectional study and self‐selected continued appropriate medical therapy or endoscopic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…ADI scores were divided into quintiles, as previously described. 27 ANOVA testing showed no significant difference correlation between any quintiles and within-subject changes in SNOT-22 or SF-6D HUV scores (Table 6).…”
Section: Bivariate Correlation Between National Adi Scores and Within...mentioning
confidence: 95%
See 1 more Smart Citation
“…ADI scores were divided into quintiles, as previously described. 27 ANOVA testing showed no significant difference correlation between any quintiles and within-subject changes in SNOT-22 or SF-6D HUV scores (Table 6).…”
Section: Bivariate Correlation Between National Adi Scores and Within...mentioning
confidence: 95%
“…19,20,22 Although indices including the neighborhooddisadvantage metric have been investigated in many diseases, the impact of this variable on CRS outcomes remains unstudied. 21,[23][24][25] Given that SES factors, including race and income, 17,18 as well as environmental exposures, 26,27 such as pollution, weather, and pollen, may all contribute to CRS pathophysiology and treatment response, 28 we sought to utilize multi-center outcomes study data to ascertain the potential impact of neighborhood disadvantage on sinonasal-specific and general QOL treatment response. As a secondary outcome, we also assessed the association between ADI and key medical comorbidities via the functional comorbidity index (FCI), a tool developed to understand the impact of 18 common comorbidities known to have a negative impact on physical function.…”
Section: Introductionmentioning
confidence: 99%
“…The mRNA expression of cytokines in nasal tissue and HNECs was examined using qRT-PCR, as previously described [15]. Briefly, total RNA was extracted using an easy-BLUE reagent (Intron Biotechnology, Seongnam, Republic of Korea), followed by cDNA synthesis from 2 µg of total RNA using the AccuPower cDNA synthesis kit (Bioneer, Daejeon, Republic of Korea).…”
Section: Quantitative Real-time Pcr (Qrt-pcr)mentioning
confidence: 99%
“…However, particles smaller than 2.5 µm can escape the nasal mucosa and travel down the lower airways. Although the pathogenesis of CRS is unclear, some studies have suggested that environmental factors are associated with its development [14][15][16]. For example, PM10 exposure significantly increased the IL-33/ST2 pathway-mediated type 2 immune response in patients with CRSwNP [17].…”
Section: Introductionmentioning
confidence: 99%